PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA OJEK ONLINE KAMPUS (STUDI PADA MAHASISWA UIN RADEN INTAN LAMPUNG FAKULTAS EKONOMI DAN BISNIS ISLAM ANGKATAN 2020) - Dwi Sheta; Dwi Ayu Puspita; Vicky F Sanjaya (STMIK Pringsewu, 2023)
Advances in technology in the field of transportation, as well as the fact that currently, the internet is very influential on citizens in living their lives have made people dependent on smartphones and the internet. This opportunity has made business founders present online-based motorcycle taxis. Application-based ordering that smartphone users easily download, both Android and iOS systems. Student activities in general are also inseparable from other supporting interests such as preparing food, managing clothing, health, and other socio-cultural activities (going to church, mosques, organizing arts and sports, and so on). Likewise, lecture activities that are all disciplined require students to be present on time, which will be directly related to the use of transportation equipment, especially online motorcycle taxis. Campus online motorcycle taxi transportation is one of the online-based motorcycle taxi service providers. Consumers only need to order via their respective smartphones if they want to go somewhere. Not only taking us, but campus online motorcycle taxis also provide food delivery services, better known as delivery orders. This study aims to analyze the influence of consumer satisfaction on campus online motorcycle taxi services. This study used a quantitative approach and analyzed data with the help of the smartpls3 program. The results showed an influence of service quality on customer satisfaction. This is evidenced by the P value of 0.000, it can be said to be influential because the P value is below 0.05.